2013
DOI: 10.1002/jgrc.20157
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Southern Ocean mixed‐layer depths in CMIP5 models: Historical bias and forcing response

Abstract: [1] The development of the deep Southern Ocean winter mixed layer in the climate models participating in the fifth Coupled Models Intercomparison Project (CMIP5) is assessed. The deep winter convection regions are key to the ventilation of the ocean interior, and changes in their properties have been related to climate change in numerous studies. Their simulation in climate models is consistently too shallow, too light and shifted equatorward compared to observations. The shallow bias is mostly associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
195
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(216 citation statements)
references
References 43 publications
(77 reference statements)
19
195
2
Order By: Relevance
“…However, in contrast to the winter, ACCESS-ESM1 appears to systematically underestimate MLDs in the high-latitude ocean in summer, 60 % (or 30-40 m) in the Southern Ocean, Pacific and Atlantic oceans. In the Southern Ocean, in particular, the underestimation of summer MLDs is consistent with Sallée et al (2013) and Huang et al (2014), who showed that most CMIP5 models underestimate summer MLDs. Huang et al (2014) attributed this to a lack of vertical mixing in CMIP5 rather than sea surface forcing related to individual models, this is consistent with Downes et al (2015), who showed that these biases are also present in the ocean-only simulations of ACCESS-ESM1.…”
Section: Sea Surface Temperature and Mixed Layer Depthsupporting
confidence: 84%
See 1 more Smart Citation
“…However, in contrast to the winter, ACCESS-ESM1 appears to systematically underestimate MLDs in the high-latitude ocean in summer, 60 % (or 30-40 m) in the Southern Ocean, Pacific and Atlantic oceans. In the Southern Ocean, in particular, the underestimation of summer MLDs is consistent with Sallée et al (2013) and Huang et al (2014), who showed that most CMIP5 models underestimate summer MLDs. Huang et al (2014) attributed this to a lack of vertical mixing in CMIP5 rather than sea surface forcing related to individual models, this is consistent with Downes et al (2015), who showed that these biases are also present in the ocean-only simulations of ACCESS-ESM1.…”
Section: Sea Surface Temperature and Mixed Layer Depthsupporting
confidence: 84%
“…4). This is encouraging given that many ocean models tend to underestimate winter MLDs (Sallée et al, 2013;Downes et al, 2015). Simulating winter mixed layers correctly is critical for setting interior ocean properties supplying nutrients to the upper ocean to fuel the biologically active growing season (Rodgers et al, 2014).…”
Section: Sea Surface Temperature and Mixed Layer Depthmentioning
confidence: 84%
“…Despite overestimating the mean carbon sinks, both HadGEM2-ES and MPI-ESM-LR reproduce the seasonal phase of the data. The MPI-ESM-LR simulates carbon uptake in the early spring period that is too strongly biologically mediated, consistent with the anomalously strong late winter mixing (August-September) (Jiang et al, 2014;Sallée et al, 2013b), which causes the required nutrients to upwell to fuel biological production. The GFDL-ESM2G, one of the two models that simulate carbon sinks closest to the data-based estimate, simulates the opposite pCO 2 seasonal phase, which is largely attributed to the bias in absolute values and amplitude of SST seasonal cycle.…”
Section: Discussionmentioning
confidence: 79%
“…They show that resultant changes in the seasonal onset of stratification influence both entrainment and the biological pump. Furthermore, Sallée et al (2013b) identify the annual mean freshwater flux as the primary source of error for the SO mixed layer depth in CMIP5 models. This uncertainty arises from the lack of accurate estimates of buoyancy fluxes from observations in the region.…”
Section: Discussionmentioning
confidence: 99%
“…One-dimensional, vertical budgets of the ocean surface boundary layer are now recognized to have limitations in reproducing observed changes in mixed layer depth (MLD), especially at subseasonal time scales (Fox-Kemper et al 2011;Belcher et al 2012;Sallée et al 2013). Three-dimensional fluid motions, typically arising from strong lateral buoyancy gradients, may be one mechanism that explains this discrepancy.…”
Section: Introductionmentioning
confidence: 99%